The Politics of Governing Resilience: Gendered Dimensions of Climate-Smart Agriculture in Kenya - Brisebois, Anouk; Eriksen, Siri Hallstrøm; Crane, Todd Andrew (Frontiers in Climate, 2022)
This paper uses climate-smart agriculture in Kenya as an empirical entry point for investigating how climate actions reshape or reinforce, gender relations, and how they are aimed at improving local resilience that is nested in such relations. While enhancing national food security, CSA practices could however reproduce inequitable power relations, such as gendered authority relations that produce vulnerability and inequalities. Equity and knowledge represent particularly contested aspects of CSA because it largely fails to address who wins and who loses from such interventions, who are able to participate while others are excluded, and whose knowledge and perspectives count in decision-making processes. Gender relations provide a stark illustration of the way that CSA fails to address how enduring inequalities of access in both production and consumption shape who is rendered vulnerable to climate change and who is left food insecure. In this paper, we treat CSA projects as a site of tensions between stability and contestation of gender relations, brought into view through moments where practices and knowledge are (re)shaped. We first review the concepts of authority, recognition, and resilience as a framework to understand how gendered inequalities and struggles over rights to resources are perpetuated within adaptation and resilience responses to climate variability. We analyze evidence from past studies regarding rural adaptation processes and gender dimensions in CSA projects to identify how such projects may modify the space for renegotiating inequitable gender relations. We approach gender relations as authority relations that are constantly internalized, resisted, and contested through practices and interactions between different actors associated with CSA projects, and the different knowledges that direct these practices. The examination focuses on Kenya as an empirical context to gain sufficient depth in understanding the social and political processes in which climate actions and gender relations are nested, enabling us to identify key points of intersection within these two themes. In addition, gendered dimensions of rural resource governance and adaptation are relatively well described in Kenya, providing lessons for how climate actions can become more gender-responsive.